Prolonged Pertussis Outbreak in Ontario Originating in an Under-immunized Religious Community - Deeks, SL (Can Commun Dis Rep, 2014)
BACKGROUND: A prolonged pertussis outbreak began in Ontario in November 2011 in an under-immunized religious community and subsequently spread to the general population and a second religious community in the same region of the province. OBJECTIVE: To compare the epidemiology in the religious communities to that of the general population within the affected jurisdictions. METHODS: The analysis includes cases reported through the integrated Public Health Information System (iPHIS) between November 1, 2011 and April 15, 2013 that met the outbreak case definition. Health unit staff assessed whether cases were members of religious communities through case investigations and collected information on immunization status, treatment and outcomes. RESULTS: A total of 443 confirmed and probable outbreak cases were reported in 7 health units. The outbreak began in one religious community (138 cases), before spreading to the general population in the region (273 cases). A second under-immunized community within the region experienced 32 cases. Thirteen cases were hospitalized and no deaths were reported. Disease peaked earlier in the religious community; cases were significantly younger, more likely to be at high risk for pertussis and more likely to be unimmunized. Among the fully immunized general population, 51% of cases were between 10-14 years and with a median of 5.6 years since their last immunization. CONCLUSION: The epidemiology of pertussis in the under-immunized community is distinct from the general population. Transmission of pertussis to the general community is not unexpected during an outbreak; however, the proportion of cases up to date with immunization warrants further investigation.